DEEP FOCUS; A DIGITAL IMAGE PROCESSING TECHNIQUE TO PRODUCE IMPROVED FOCAL DEPTH IN LIGHT MICROSCOPY - Goldsmith, Noel T (Image Analysis and Stereology, 2011)
In light microscopy, the spatial transverse resolution is a function of the wavelength and numerical aperture. The depth resolution is another function of these parameters. The factors that enable the detection of fine detail, make the sharp focusing of more than a thin slice of the depth in an object impossible. When the examination of fracture surfaces is attempted using light reflection microscopy, the roughness will often restrict the in-focus parts of an image to a small portion of the field of view. Several authors have presented methods that enable a set of digitised images to be processed into a single composite image which contains the in-focus parts from each image. These methods are effective, unfortunately the noise present in each digital image is accumulated, resulting in increasingly noisy composite images as the number of images in a set is increased. During processing, a separate image depicting the heights in the surface, i.e. a contour map, may be produced. This image is the key that enables the production of an in focus composite image which does not accumulate noise. Image analysis under computer control will frequently require the use of automatic focusing. Several authors have published criteria which may be used to determine the state of focus of an image. Such criteria have a clear application to the above process. This paper presents an evaluation of some methods used for the processing of such images, and also some procedures used for the determination of sharpness of focus and demonstrates a sensitive method for the evaluation of such procedures. Finally, an implementation of a method which uses the one of the simplest focus criteria is presented, and a procedure for the production of deep focus images which are free from the accumulation of noise.